Integrating Theology in Teaching Quantitative and Qualitative Research in Psychology - Pak, Jenny Hyun Chung (Journal of psychology and christianity, 2023)
Historically, quantitative and qualitative researchers have fundamentally disagreed about the methodology used to discover truth. Differences between these approaches have been philosophically debated over which method is best. In part, key differences stem from varying epistemological foundations and assumptions inherent in quantitative and qualitative research. Because "pure data" or facts do not exist apart from interpretation, whether quantitative or qualitative, the most valuable aspects of research are interpretive and reflexive activities. Because methods cannot be viewed independent from theory and other elements of preunderstanding (e.g., socio-political and cultural background, research community, language), researchers must actively engage in critical reflection. Qualitative and quantitative methods have different strengths and weaknesses and are best suited to answer different research questions. At the heart of integrating psychology and theology are beliefs regarding the etiology and revelation of truth. According to practical theology, all human practices emerge from and seek to participate in God’s wider project in the world (i.e., God’s practices) and understanding the reign of God. All Christian activities, including integrating theology and quantitative and qualitative research, reflect and interpret the nature and purpose of God’s practices in history.